Enzyme leakage from spermatozoa of Black Bengal and beetal bucks during freezing with various cryoprotectants - SINGH, M P; SINHA, A K; SINGH, BALRAJ; SINGH, D K (The Indian Journal of Animal Reproduction, 2023)
The present experiment was conducted to study the effect of cryoprotectants (glycerol, DMSO + IJ and lactose) containing extenders on leakage of acrosin and hyaluronidase enzymes from spermatozoa of Black Bengal and Beetal bucks. Activities of acrosin and hyaluronidase were assayed in neat, equiliberated (pre-freezing) and frozen thawed (post-freeze) semen samples. The variations in acrosin activity at pre- and post-freeze stages due to extender were significant (P<0.01). Mean intracellular acrosin activities in the neat semen of Black Bengal and Beetal bucks were 0.0275± 0.00084 and 0.0301± 0.00105 units/109 sperms, respectively. Acrosin activity decreased inequiliberated and frozen thawed semen as compared to neat semen, indicating the cryoprotective ability of extenders. Extracellular mean activities of hyaluronidase in the neat semen of Black Bengal and Beetal bucks were 233.78 ±12.688 and 220.58±7.261 units/109 sperms. Hyaluronidase activity increased in equiliberated and frozen thawed semen as compared to neat semen. It also indicate cryoprotective properties of extenders.